Degradation of emerging contaminants from water under natural sunlight: The effect of season, pH, humic acids and nitrate and identification of photodegradation by-products. (November 2015) - Koumaki, Elena; Mamais, Daniel; Noutsopoulos, Constantinos; Nika, Maria-Christina; Bletsou, Anna A.; Thomaidis, Nikolaos S.; Eftaxias, Alexander; Stratogianni, Georgia
Graphical abstract: Highlights: Direct photolysis is more efficient than indirect photochemical processes. Half-lives of most compounds depend on season and light intensity. Some phenolic compounds are more reactive in the presence of humic acids. Emerging contaminants' transformation in water can be photosensitized by nitrates. The toxicity of the identified by-products of KTP and DCF needs to be investigated. Abstract: Both photodegradation and hydrolysis of non-steroidal anti-inflammatory drugs (NSAIDs) and endocrine disrupting chemicals (EDCs) were investigated in order to evaluate their photochemical fate in aquatic environment and to assess the effect of season and specific characteristics of water (pH, humic acids and nitrate concentration) on the removal of target EDCs and NSAIDs through photodegradation. An additional objective was the identification of the photodegradation by-products of specific NSAIDs and their dependence on irradiation time. Selected compounds' transformation was investigated under natural sunlight radiation while control experiments were conducted in the dark. As expected, most of compounds' degradation rate decreased with decreasing light intensity between two different experimental periods. Most of the tested compounds exhibited different rates of degradation during direct and indirect photolysis. The degradation rate of the selected compounds increased in the presence of NO3 − and the photodegradation rate was higher for some compounds in alkaline than in acidic solution. The effect of humic acids' presence in the water depends on the absorbance spectrum of the compound and the produced photosensitizers. More specifically, humic acids act as inner filter toward most of the selected NSAIDs and as photosensitizers toward most of the EDCs. The results of the irradiation experiments in the presence of both humic acids and NO3 −, indicate that the direct photolysis is much more efficient than indirect photochemical processes. Finally, several degradation by-products of ketoprofen and diclofenac were identified in the samples, exposed to sunlight. The dependence of these by-products on radiation time is also demonstrated.